Challenges of providing of special care services in hospitals during emergencies and disasters: a scoping review - Mohammad Masbi; Nader Tavakoli; Mohsen Dowlati (BMC Emergency Medicine)
Abstract Background The ability of hospitals to provide special care services for critically ill or injured patients during emergencies and disasters poses very significant challenges that necessitate the response in-place plans. the increasing frequency of such events, coupled with limited hospital resources and increasing patient volumes, underscores the urgency of addressing these issues. Specifically, this study aims to identify the challenges faced by hospitals in providing special services during disasters. Method This scoping review, conducted in 2024, based upon the framework developed by Arksey and O’Malley. An extensive search of Literature searching was performed using gray literature and databases including Google Scholar, PubMed, Web of Science, and Scopus. Applying the selection criteria, a total of 33 relevant studies were identified that discuss the challenges faced when providing special care services in hospitals during emergencies and disasters. Results are presented in accordance with the PRISMA checklist to ensure quality and transparency. Data was analyzed through a systematic coding process where common themes across the studies were identified. Results This review identified 15 distinct challenges associated with providing special care services in hospitals during emergencies and disasters: limited resources, inadequate infrastructure, lack of pre-hospital care, financial constraints, failures in the emergency response system, triage, deficiencies in management structure, planning, and preparation, communication and coordination deficits, training and protocols development, employee welfare challenges, challenges of continuity of care, increased demand, different and complex needs of patients, ethical challenges, imbalance in distribution of service resources. Conclusions Response in a hospital to the needs of special care during a disaster has to be responded to with more effective preparedness through comprehensive disaster preparedness plans, better communication and coordination, and training of staff and allocation of resources. In particular, standardized triage protocols and ethical frameworks will provide the foundation for the optimization of resource use in emergency responses. Better communication among departments and also with other outside organizations will improve how resources are used to better achieve good patient outcomes within emergency responses.